Karakteristik Penderita Infeksi Pasca Operasi Fiksasi Interna Ekstremitas Bawah di Instalasi Bedah Pusat RSUP Haji Adam Malik Medan Periode Januari 2012 - Juni 2014 - Fahmi, Ichsan; Siregar, Chairiandi (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Introduction The surgical site infection in Orthopaedic surgery is a serious problem for both the patient and surgeonMethods This study was conducted using retrospective descriptive method using medical record data of the patients that underwent internal fixation surgery of the lower extremities in RSUP H. Adam Malik Medan within the period of January 2012 â June 2014. The characteristics assessed in this study include stage, gender, site of the infection, history of internal fixation surgery (implants) and risk factors.Results There were 25 patients (5.9%) out of 420 sample that developed infection with characteristics, 23 were male (92%) and 2 were female (8%). There were 11 patients (42%) aged less than 30 years old, 11 patients (42%) aged 30-60 years old, and 3 patients (12%) aged above than 60 years old. According to the site of the infection it is found that there were 13 patients has infections originating from the femur (52%), tibial area 8 patients (32%), ankle area 1 patient (4%) and the combination of multiple sites are 3 patients all together. From the data of 25 patients that developed infection it is found that there were 4 smokers and 2 patients suffering from diabetes and 3 elderly patients (above 60 years old).Conclusion: Patients developing infection post internal fixation surgery of the lower extremities in RSUP H. Adam Malik are still considered high. In this study, the risk factor relating to the surgical site infection is unclear although it is known that the risk factors such as elderly age, duration of operation, smoker, diabetes mellitus, length of stay in the ward and mucosal damage around the fracture site causes one to develop infection.Keywords : : internal fixation purgery, post operation, infection, risk factor